285 The sharing economy: hazards of being an uber driver. (24th April 2018) - MacEachen, E; Reid Musson, E; Bartel, E; Carriere, J; Meyer, SB; Varatharajan, S; Kosny, A; Bigelow, P; Saunders, R
Abstract : Introduction: Uber ride-sharing is an important sharing economy challenge. The taxi industry is notoriously dangerous; even regulated and licensed professional drivers face a homicide rate higher than police officers and first responders. Uber drivers lack special licenses, organised workplaces and other usual safety structures. However, Uber touts different safety features, including feedback and ratings. Our study is focused on understanding the day-to-day work conditions and risks of Uber drivers. Method: We conducted a critical interpretive study of ride sharing with Uber drivers, passengers and management, taxi managers and related policy makers in Ontario, Canada. Data include interviews and focus groups with 50 drivers, passengers, taxi and Uber managers and key informants. These were recorded verbatim, coded and analysed using strategies of coding, indexing and charting in a framework analysis. Results: Uber drivers face unique risks relating to insurance coverage, the driver rating system, financial incentives, and asymmetric information. Drivers were not disclosing their ride sharing activity to their personal auto insurers in order to avoid premium hikes, thereby risking fraud charges and insurance cancellation. The Uber driver rating system prompted drivers to tolerate difficult and hazardous rides to avoid the risk of low ratings by passengers. Drivers received incentives to drive even when they were trying to sign off. Finally, passenger destination was blinded to the driver, creating asymmetric information conditions that limited driver choice of ride destination and duration. Conclusion: Many of the driver risks related to drivers' own precarious economic situations and need for income together with pressures from the Uber app to engage in unsafe working conditions. Although Uber drivers are touted as only 'sharing' a ride and as their 'own boss', in practice their driving activities were strongly governed by the Uber app